Students’ perceptions toward their motivation during the online learning - Prasetyo, Dodi Erwin ((JELE) Journal Of English Language and Education, 2021)
There were rare researches undertaking the study to analyse senior high school students’ perceptions toward their motivation during e-course. Therefore, this study was to observe their motivation during e-course and was to identify male and female students’ differences for their motivation during e-course. This study engaged 27 senior high school students in East Java, 21 female and 6 male. This study employed quantitative descriptive with Mann Whitney analysis to observe their motivation differences. The results underlined that (1) mostly students interested to gather ideas during e-course. (2) They interested to evolve their own ideas. (3) Majorities of students liked in completing their individual tasks. (4) They also enjoyed group assignments. (5) Most of students tended to ask a teacher toward incomprehensive material parts. (6) They felt attractive to do group discussion during e-course. In addition, there were no differences between male and female students on their motivation during e-course. It was proved by significance two tailed at .464 upper than .05.  Suggestions are provided for a pedagogic and future research.